Communication and influence - Andrea Prat; Joan de Martí; Antoni Calvó-Armengol (Theoretical Economics, 2015)
We study the information flows that arise among a set of agents with local knowledge and directed payoff interactions, which differ among pairs of agents. First, we study the equilibrium of a game where, before making decisions, agents can invest in pairwise active communication (speaking) and pairwise passive communication (listening). This leads to a full characterization of information and influence flows. Second, we show that, when the coordination motive dominates the adaptation motive, the influence of an agent on all his peers is approximately proportional to his eigenvector centrality. Third, we use our results to explain organizational phenomena such as: the emergence of work cliques; the adoption of human resources practices that foster communication (especially active communication); and the discrepancy between formal hierarchy and actual influence.
Keywords: D83; D85; 330; Team theory; organizations; communication; invariant method